Formulation, in-vitro and in-vivo pharmacokinetic evaluation of simvastatin nanostructured lipid carrier loaded transdermal drug delivery system - S Brito Raj; Kothapalli Bonnoth Chandrasekhar; Kesavan Bhaskar Reddy (SpringerOpen, 2019)
Abstract Background A simvastatin nanostructured lipid carrier loaded transdermal patch was developed to enhance the bioavailability and therapeutic effect. Methods Simvastatin NLC preparation was prepared by optimized hot homogenization technique and were characterized by particle size in nanometer, polydispersity index, zeta potential in millivolt, scanning electron microscopy, and entrapment efficiency by applying Box Behnken design utilizing multiple linear regression method. Results Chosen optimized NLC F7 formulation has particle size of 125.4 ± 2.66 nm, zeta potential of − 33.6 ± 2.42 mV, and PI of 0.480 ± 0.24. The NLC was loaded in transdermal patch by solvent evaporation method and evaluated for physical characteristics, drug content, skin permeation studies, and in-vivo pharmacokinetic studies in male albino Wistar rat. In-vivo pharmacokinetic studies in NLC loaded transdermal patch show an increase in AUC0-α in mg/ml when compared to marketed oral dosage form, which confirms the enhancement of bioavailability of simvastatin by NLC loaded transdermal patch. Conclusions From the data, it was concluded that drug-loaded NLC transdermal patch will be a promising drug delivery system for poorly bioavailable drugs.